Generation of phenotypically normal marker-free transgenic plants of Kalanchoe blossfeldiana through hairy root induction - Thirukkumaran, G.; Ntui, V.O.; Khan, R.S.; Nakamura, I.; Mii, M. (The Japanese Society for Plant Cell and Molecular Biology., 2010)
Multi-Auto-Transformation (MAT) vector system consists of positive selection, using the ipt or rol gene, with a site-specific recombination and DNA removal system, that generates morphologically normal marker-free transgenic plants without antibiotic selective-agent. This study describes rol-type MAT vector (pMAT101) containing lacZ gene as a model gene and the removable cassette with gus gene in the T-DNA region which was used to produce morphologically normal transgenic Kalanchoe blossfeldiana Poelln. employing rol gene as the selectable marker gene and gus gene as a reporter gene. Leaf explants inoculated with pMAT101 produced hairy roots with GUS expression on agar-solidified, half-strength MS medium without both plant growth regulators and selective agent under dark condition. These hairy roots produced shoots with Ri syndrome such as dwarfism, wrinkled leaves, and an over abundance of roots as a consequence of the morphogenic action of rol gene. They eventually produced morphologically normal shoots without GUS expression on the same fresh MS medium under 16h photoperiod. Molecular analysis of DNA from the hairy roots, shoots with Ri syndrome and morphologically normal shoots revealed that the normal shoots had only lacZ gene, and the removable cassette consisting of rol, R (recombinase) and gus genes was excised. This study indicates that the rol-type MAT vector could be used for the production of morphologically normal marker-free transgenic K. blossfeldiana plants without using selective chemical agents.
Keywords: Kalanchoe blossfeldiana; MAT vector; Removable cassette; Rol gene; Site-specific recombination